Pemberdayaan Ekonomi Transformatif: Upaya Pemanfaatan Lahan Kosong Untuk Peningkatan Pendapatan - Tohawi, Agus; Iswanto, Juni; Nasrullah, Aan (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
The objectives of this service include, first, using vacant land in the yard of residents' houses to plant horticultural crops, second, making horticultural crops a productive plant and can be used as additional income, and third, in the long term Jatikalen Village can be used as a plant tourism village. horticulture. The service approach used by researchers is PAR (Participatory Action Research). The results of this service are (i) Public awareness, especially housewives in Jatikalen Village, Jatikalen District, regarding the use of empty yards has been awakened because the community previously had no motivation to use the vacant land. After the training and mentoring, the situation can slowly change in a positive direction, (ii) the community knows how to properly cultivate horticultural crops using polybek media, with results that are not inferior to planting directly on the ground, (iii) the community knows and understand the advantages and disadvantages of cultivating with polybek media, (iv) the community will understand how to make compost and starter fertilizers, which do not use pesticide fertilizers, (v) Establishment of a body to accommodate the results of this horticultural crop harvest.